Calcium Homeostasis Comparison in Thermal Burn Patients–Early Tangential Excision and Grafting versus Conservative Management - Jha, Sonika; Goyal, Parul; Bhattacharya, Sameek; Baranwal, Shilpi (Indian Journal of Plastic Surgery, 2020)
Introduction With the advent of better burn wound management protocols, early excision and grafting, increased number of burns patients are surviving and entering the struggle of prolonged rehabilitation. Calcium homeostasis and its influence on bone mineralization plays an important role, but it is adversely influenced by the proinflammatory state in burns, leading to hypocalcemia and paradoxical hypercalciuria which, in turn, leads to excessive bony resorption and pathological fractures. The role of early excision in the overall metabolism of calcium is being investigated in the study.Method This study was undertaken in a tertiary level government-run hospital from February 2018 to August 2019. A total of 28 patients with second degree thermal burns were included. For all patients, fasting serum parathormone levels along with various serum electrolytes like Ca2+, Mg2+, PO43- and urinary calcium levels were serially measured from day of admission to 2 months. The first group of 14 patients (Group A) underwent early tangential excision and skin grafting, whereas another 14 patients (Group B) underwent conservative management. All categorical variables were analyzed with the help of Chi square test. A p value of < 0.05 was considered statistically significant.Result There was a statistically significant improvement in serum parathormone and other electrolytes’ levels in the tangential excision group. Similarly, urinary excretion of calcium also showed favorable results in the group.Conclusion Early tangential excision and grafting in burns plays an important role in maintaining serum parathormone and calcium levels, leading to prevention of hypercalciuria and optimization of other factors affecting calcium homeostasis.
Keywords: homeostasis; hypercalciuria; hypocalcemia; parathormone; tangential excision